Factors Associated with Women's Readiness for Menopause: A Literature Review - Riska Marlin (Jurnal Kesehatan Budi Luhur: Jurnal Ilmu-Ilmu Kesehatan Masyarakat, Keperawatan, dan Kebidanan, 2026)
Menopause is a physiological phase experienced by women due to declining reproductive function and is often accompanied by physical and psychological changes that may affect quality of life. Women's readiness to face menopause is influenced by various internal and external factors. This study aimed to identify factors associated with women's readiness for menopause based on published research findings. This study employed a literature review method using the PRISMA approach. Article searches were conducted through Google Scholar, PubMed, ScienceDirect, and Garuda using keywords related to menopause readiness. The selected articles were original research studies published between 2020 and 2025. A total of 20 articles met the inclusion criteria and were analyzed. The results showed that factors associated with women's readiness for menopause included knowledge, educational level, family and husband support, psychological factors, health education, and socioeconomic conditions. Knowledge and family support were identified as important factors contributing to better readiness for menopause. Women's readiness for menopause is influenced by multiple interrelated factors. Health education and family support are needed to help women experience menopause with better preparation and positive adaptation.